2014
DOI: 10.1099/vir.0.058958-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of subclinical prion disease in aged mice following exposure to bovine spongiform encephalopathy

Abstract: The occurrence of variant Creutzfeldt–Jakob (vCJD) disease in humans was almost certainly the result of consumption of food contaminated with bovine spongiform encephalopathy (BSE) prions. Despite probable widespread exposure of the UK population to BSE-contaminated food in the 1980s, vCJD has been identified predominantly in young individuals, and there have been fewer cases of clinical disease than anticipated. The reasons for this are uncertain. Following peripheral exposure, many prions replicate within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 53 publications
(88 reference statements)
6
39
0
Order By: Relevance
“…Although many of these changes were most prominent in mice ≥ 18 months old, significant disruption to the MAdCAM‐1 + MZ sinus lining cells was evident from as early as 9 months old and preceded the changes to MZ B cells observed at 12 months. Hence these data show that significant ageing‐related changes are evident in the splenic MZ much earlier than has been previously described 6, 7, 8. The timing of the changes observed also suggests that the ageing‐related disturbances to the distribution of the MAdCAM‐1 + MZ sinus lining cells may lead to subsequent disturbances to the distribution of MZ B cells and MZ metallophilic macrophages.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Although many of these changes were most prominent in mice ≥ 18 months old, significant disruption to the MAdCAM‐1 + MZ sinus lining cells was evident from as early as 9 months old and preceded the changes to MZ B cells observed at 12 months. Hence these data show that significant ageing‐related changes are evident in the splenic MZ much earlier than has been previously described 6, 7, 8. The timing of the changes observed also suggests that the ageing‐related disturbances to the distribution of the MAdCAM‐1 + MZ sinus lining cells may lead to subsequent disturbances to the distribution of MZ B cells and MZ metallophilic macrophages.…”
Section: Resultssupporting
confidence: 67%
“…Our laboratory has previously demonstrated this in 20‐month‐old C57BL/Dk and RIII mice,6, 7 and an independent study has reported disturbances to the MZ in C57BL/6 mice > 12 months old 9. Others have also demonstrated changes to the MZ of 17‐ to 18‐month‐old BALB/c mice 8.…”
Section: Resultsmentioning
confidence: 67%
“…Studies using transgenic mice expressing human PrP C suggest that the transmission of BSE to humans is restricted by a significant species barrier [74]. After interspecies prion exposure, the processing and amplification of prions upon FDC in lymphoid tissues is important for their adaptation to the new host and to achieve neuroinvasion [75, 76]. Thus, it is plausible that factors which increase the density of M cells in the small intestine may enable a greater burden of prions to enter Peyer’s patches, increasing the probability that more will be able to avoid clearance by cells such as macrophages, [11, 77].…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms behind high permissiveness of lymphoid tissues to prions are not known, prions acquired via cross-species transmission can persist stably and silently in SLOs for a long time in the absence of neuroinvasion (15,56,57). Aged animals that are known to be less susceptible to prion infection than young animals can also accumulate prions within their lymphoid tissues, despite lack of prions in their brains (58). Moreover, the lymphoid tissues display a higher capacity than nerve tissues to replicate prions after low-dose infection (59).…”
Section: Discussionmentioning
confidence: 99%